Benzilaminopurina e ácido naftaleno acético na indução e multiplicação in vitro de gemas de abacaxizeiro da cultivar IAC Gomo-de-mel - Fraguas, Chrystiane Borges [UNESP]; da Vitoria Dornelles, Carolina Martins [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (Universidade Federal de Santa Maria (UFSM), 2009)
The objective of this research was to evaluate the effects of BAP (6-benzyl amino purine) and NAA ( naphthalene acetic acid) on in vitro buds induction and multiplication on Ananas comosus cv. 'IAC Gomo-de-mel' shoots and its correlation with the peroxidase activity and soluble protein content. Axillary buds were excised from the healthy fruits crown and inoculated in MS solidified with agar at 5 % and pH adjusted to 5.7 with the treatments that included different concentrations and combinations of BAP (0, 0.5, 1.0 e 1.5mg L(-1)) and NAA (0, 0.5 e 1.0mg L(-1)). At, 65 days stage, 2.24 shoots were formatted using BAP 1mg L(-1). After bud development, which were inoculated in MS liquid medium associated with two treatments (1.0 mg L(-1) BAP + 0.5mg L(-1) NAA e 1.0mg L(-1) BAP + 1.0mg L(-1) NAA). At 95 days the medium more appropriate was 1.0mg L(-1) BAP + 0.5mg L(-1) NAA, providing 7.42 shoots and lower hyperhydricity percentage, more shoots induction and buds. The total soluble proteins showed negative relationship with hyperhydricity and shoots length. The peroxidase activity was higher in plants with more shoots and greater hyperhydricity percentage.
In vitro bud induction and multiplication of cv. IAC Gomo-de-mel pineapple fruit with benzyl amino purine and n aphthalene acetic
Keywords: Ananas comosus; tissue culture; peroxidase; hyperhydricity